Direct and Real‐Time Quantification of Tenofovir Release from pH‐Sensitive Microparticles into Simulated Biological Fluids Using 1H Nuclear Magnetic Resonance. Issue 4 (19th February 2014) - Zhang, Chi; Zhang, Tao; Oyler, Nathan A.; Youan, Bi‐Botti C.
<x xml:space="preserve">Abstract</x> In vitro drug release evaluation is a very important step toward the quality control of nano‐ or micro‐particular drug delivery systems. However, most quantitative techniques such as high‐performance liquid chromatography requires a dialysis membrane to separate the released free drug from these delivery systems, thus are not capable of direct detection and real‐time quantification of the drug release kinetics. This study describes, for the first time, a rapid, specific, and direct method for the real‐time quantification of in vitro tenofovir (TNF) release from pH‐sensitive microparticles using a Varian 400 MHz 1H nuclear magnetic resonance (1H‐NMR) spectrometer. Various analytical performance parameters such as linearity, precision, accuracy, limit of quantification, limit of detection, and robustness were validated according to International Conference on Harmonization (ICH) guidelines. The in vitro release of TNF from microparticles in both simulated vaginal fluid (VFS) and the mixture of VFS and simulated semen fluid was monitored and quantified in real time using 1H‐NMR. The capability of real‐time quantification of in vitro drug release from microparticles not only provides a more accurate prediction of its biological behavior in vivo, but is also independent of potential interference from the dialysis membrane. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:1170–1177, 2014